Religiusitas, Konseptual dan Adaptif Terhadap Kinerja Relawan Pajak di Universitas Islam Negri Maulana Malik Ibrahim Malang - Raudatul Jannah; Sri Andriani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the effect of religiosity, conceptual and adaptive on the performance of tax volunteers. This study uses quantitative methods using multiple linear regression analysis. To determine the sample, the researcher used a non-probability sampling technique with purposive sampling measurement. Therefore, the survey was conducted on 100 respondents, namely individual income taxpayers who have been assisted by tax volunteers in the tax reporting process. Researchers distributed questionnaires through Google Form. The results of this study indicate that the independent variables, namely religiosity, conceptual and adaptive have a significant effect on the dependent variable, namely the performance of tax volunteers. The results of the analysis of the variables that most dominantly affect the performance of tax volunteers are adaptive.